Tuna Fishery Resources Supply Chain (Thunnus sp) in Maumere District, Sikka Regency, East Nusa Tenggara Province - Alpiani Alpiani (Hasanuddin University, 2022)
The potential of Maritime Affairs and Fisheries owned by Indonesia becomes a massive opportunity in producing various types of commodities provided by natural resources such as the fishing fish, aquaculture, fishery products, and ecotourism. Based on this, it is necessary to have synergy between the government, the private sector and the community in managing marine fisheries resources that exist today. Of course, with the existing potential, it will become a challenge in its management that can guarantee the sustainability of natural resources and the improvement of the people's economy. This paper examines the opportunities and challenges of the fishing industry in Indonesia using the input and output data of the Directorate General of Maritime and Fisheries Resources Supervision, which are analyzed descriptively using tables and graphs and journal reviews relating to the study.